Experimental investigation of the natural convection heat transfer characteristics of cylinder walls with a DBD actuator as the heat source. (August 2022) - Zhao, Qijin; Mao, Baoquan; Chen, Chunlin; Liao, Zili; Zhang, Xinxi; Bai, Xianghua; Chen, Luming
Abstract: Conventional electric heating methods applied when evaluating the natural convection heat transfer parameters at the outer walls of cylinders produce uneven heat flows and large measurement errors. The present work addresses these issues by developing a new heating method using a dielectric barrier discharge (DBD) actuator as the heat source. An experimental system is constructed, where the thermal power output of the DBD actuator is first measured by calorimetry, and the natural convection heat transfer characteristics of a representative cylinder are analyzed with an explicit accounting of the temperature distribution at the outer wall of the cylinder. The results demonstrate that the DBD actuator can provide more uniform heat flow than conventional electric heaters. The temperature difference between the top and the bottom of the cylinder wall initially increases with increasing thermal power, decreases to a minimum at a thermal power of about 400 W, and subsequently increases with increasing thermal power. In addition, and the feasibility of the DBD actuator as a heat source is demonstrated according to the high degree of conformation between the calculated values and empirically established correlations between Nusselt number, which generally deviate by less than 10%.